Consumer knowledge, perceptions, practices and barriers relating to organic foods - Johannesburg, Gauteng Province, South Africa - Erasmus, Nina Ariel (Stellenbosch : Stellenbosch University, 2020)
(Thesis (MNutr)--Stellenbosch University, 2020.